(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the association between nutritional risk assessed by the NRS-2002 score and the incidence of ventilator-associated pneumonia in cardiovascular intensive care unit patients. Methods: A cross-sectional study with longitudinal follow-up was conducted on 98 mechanically ventilated patients. Nutritional risk was assessed using NRS-2002. Data on ventilator-associated pneumonia incidence, causative bacteria, duration of mechanical ventilation, and mortality were recorded. Results: The incidence of ventilator-associated pneumonia was 15.3%, with a density of 28.09 cases/1000 ventilator days (95% CI: 15.72-46.33), predominantly late-onset ventilator-associated pneumonia (93.3%). Overall mortality was 46.9%. The main pathogens included A.baumannii (40%), P.aeruginosa (26.7%), K.aerogenes (26.7%), K.pneumoniae (13.3%), S.aureus (16.3%), E.coli (6.7%), and A.berezinae (6.7%). Patients with high nutritional risk (NRS-2002 ≥ 3 points) had a significantly higher ventilator-associated pneumonia rate compared to low-risk patients (29.8% vs 2%, p < 0.05), with a 19-fold increased risk of ventilator-associated pneumonia. Ventilator-associated pneumonia was associated with higher mortality (73.3% vs 42.2%, p = 0.026) and longer mechanical ventilation duration (9.27 days vs 4.75 days, p = 0.01). Conclusion: Nutritional risk assessed by NRS-2002 is an independent risk factor for ventilator-associated pneumonia in cardiovascular intensive care unit patients. Early nutritional assessment and intervention are essential to reduce this complication.